Secretly yours : a novel - Bailey, Tessa (Avon, an imprint of HarperCollinsPublishers, 2023)
Returning home to his family's California winery, Professor Julian Vos, on sabbatical from his Ivy League job, finds himself distracted from his plans to write a novel by eccentric, chronically late, unbelievably beautiful gardener Hallie Welch, who is a burst of color in his gray-scale life.